Performance assessment of density and level-set topology optimisation methods for three dimensional heat sink design. Issue 3 (September 2018) - Santhanakrishnan, Mani Sekaran; Tilford, Timothy; Bailey, Christopher
In this paper, two most prevalent topological optimisation approaches namely Density and Level set method are applied to a three dimensional heat sink design problem. The relative performance of the two approaches is compared in terms of design quality, robustness and computational speed. The work is original as for the first time it demonstrates the relative advantages and disadvantages for each method when applied to a practical engineering problem. It is additionally novel in that it presents the design of a convectively cooled heat sink by solving full thermo-fluid equations for two different solid-fluid material sets. Further, results are validated using a separate computational fluid dynamics study with the optimised designs are compared against a standard pin-fin-based heat sink design. The results show that the Density method demonstrates better performance in terms of robustness and computational speed, while Level-set method yields a better quality design in terms of final objective value.